The Effect of natural organic manure on the growth and productivity ofpotato (solanum tuberosum Z var spunta) in a Sahara desert region - Ghemam Amarad, D.; Senoussi, M. M. (University of Eloued جامعة الوادي, 2013)
Many studies have been carried out on the growth, productivity and nutritional properties of potato, including the effects of organic manures on tuber yield and quality. However, there are few studies on the effect of organic manure on potatoes agriculture in arid zones. The main objective of this study was to investigate the effects of natural organic manure on the growth and productivity of potato (Solanum tuberosum, cv. Spunta) in a Saharian region (El-oued, Algeria). An experiment was laid out out in a randomized complete block design (RCBD), with four replications and five labeled treatments, the control (no manure), the common fertilization treatment applied by the potatoes farmers 2 q/h (15-15-15 NPK) + 25 t/h poultry manure, 50 t/h of poultry manure, sheep manure and 50 t/h of mixed manure poulty and sheep 1:1 w/w. Results showed an increase in the foliage area, plant cover area and the number of stems per plants by adding poultry manure, and mixed manure more treatments of mixed manure (poultry and NPK) or sheep manure in comparison with control (no manure). The treatment by mixed manure showed significant increase in the number of tubers per plant in comparison with other treatments, but all the used treaments caused a significant increase in the tuber weights and the quantity of production and the percent of standard tubers in comparison with control. The treatments with poultry manure gave the hihest yied in increasing the yield with high significant difference incomparison to other treatments. Thus, the combination of natural organic manures and low rates of inorganic fertilizers is a promising low cost option in production of high yields of potatoes.
الملتقى الدولي الرابع حول التصرف وتنمية الموارد والتطبيقات البيو تكنولوجية في الأنظمة الزراعية الجافة والصحراوية 17-19 ديسمبر 2013 معهد المناطق القاحلة مدنين تونس
Keywords: Potato, Organic Fertilizer, Growth, Yield